Proceedings of the Proceedings of the Third Workshop on Multidisciplinary and Its Applications, WMA-3 2019, 11-14 December 2019 2020
DOI: 10.4108/eai.11-12-2019.2290848
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Project Based Learning on Writing Business Letters

Abstract: This research investigated the implementation of the use of PBL in improving the students' writing ability. The objectives of this research was to find out whether there is a significant effect of using PBL toward writing ability or not. This research is colaborating between english lecturer and development economic lecture where the output of this research is a module (a material collection of writing business letters technique including the sample). This research was carried out on the third semester student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It is also in line with the research conducted by (Wardani et al, 2021), which found that project-Based Learning also revealed potentially promotes students' critical thinking, creativity, and collaborative work and enhances teachers' satisfaction in teaching. The other research on PjBL, as conducted by (Argawati & Suryani, 2020;Fatmawati, 2021;Ramadhani et al, 2020), also found the advantages of PjBL in enhancing students' writing ability.…”
Section: Wulandari Et Al (2023)mentioning
confidence: 85%
“…It is also in line with the research conducted by (Wardani et al, 2021), which found that project-Based Learning also revealed potentially promotes students' critical thinking, creativity, and collaborative work and enhances teachers' satisfaction in teaching. The other research on PjBL, as conducted by (Argawati & Suryani, 2020;Fatmawati, 2021;Ramadhani et al, 2020), also found the advantages of PjBL in enhancing students' writing ability.…”
Section: Wulandari Et Al (2023)mentioning
confidence: 85%
“…The business letter serves as a crucial communication tool and written documentation employed for exchanging information between firms. Its primary purpose is to impart comprehensive and pertinent information aligned with the company's objectives (Ramadhani et al, 2019). A well-crafted business letter constitutes a formal written statement designed to convey crucial information to other corporate entities, serving as a means of communication essential to the functioning of businesses.…”
Section: Introductionmentioning
confidence: 99%
“…Although these references are similar to the researcher, the researcher also find these references different from the present studies because the researcher focuses on the categorized linguistic errors and backed up with the difficulties that the students experience so that the study shall be provide solution in writing business letters. Ramadhani and Sir (2018), Villoso and Medalla (2019), Guice and Sims (2020), and Sanu (2016)focused on innovative techniques in teaching business letter writing to the students such as utilizing flipped classroom, process oriented skill through portfolio assessment, and experimental way of teaching. Their strategies are significant in developing the various ways of teaching students to capture their interest and engage them more business letter writing.…”
mentioning
confidence: 99%